2014
DOI: 10.1080/10665684.2014.959284
|View full text |Cite
|
Sign up to set email alerts
|

Redefining Possible: Re-Visioning the Prison-to-College Pipeline

Abstract: This article identifies college as the logical space for the articulation of civil rights through the complete integration of students with incarceration histories into the intellectual and social fabric of the institution. Academic institutions provide a fertile ground where possibilities for personal and social change are realized, networks are opened, knowledge is contributed and developed, and giving back is enabled. Using interview and focus group data collected from The Gifts They Bring, a participatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Educational programming inside prisons increases the likelihood of acquiring educational and employment opportunities upon release thus greatly reducing their chances for recidivism. Correctional facilities are overcrowded with mostly low-level non-violent offenders and at least 95% of nearly 2.5 million persons incarcerated will be released at some point (Alexander, 2010; Halkovic, 2014). In fact, correctional facilities release approximately 700,000 incarcerated persons each year to local communities (Carson & Golinelli, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational programming inside prisons increases the likelihood of acquiring educational and employment opportunities upon release thus greatly reducing their chances for recidivism. Correctional facilities are overcrowded with mostly low-level non-violent offenders and at least 95% of nearly 2.5 million persons incarcerated will be released at some point (Alexander, 2010; Halkovic, 2014). In fact, correctional facilities release approximately 700,000 incarcerated persons each year to local communities (Carson & Golinelli, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Quality educational and vocational opportunities inside correctional facilities improve an incarcerated person’s likelihood of program completion (Fine, 2013; Halkovic, 2014; Karpowitz, 2017; Marquez-Lewis et al, 2013; Patton, 2012; Torre & Fine, 2005). Furthermore, these programs are predictive of securing employment upon release from prison 1 (Davis, Bozick, Steele, Saunders, & Miles, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…6 – 8 HEPPs provide opportunities for students to earn GEDs and/or post-secondary degrees and engage in training opportunities. 6 , 9 13 However, access to such programs varies substantially by geographical region. For example, Royer et al reported that while North Carolina has 44 HEPPs, seven states only had one and three states offer none.…”
Section: Challenge Statementmentioning
confidence: 99%
“…Nearly twenty years later, Bureau of Justice Statistics data on individuals released from custody in 2005 reports 67.8% of inmates return to prison within three years of release and 76% returned within five years of release; with 56% of those being re-arrested within the first year (Bureau of Justice, 2018). Studies also indicate inmates who participate in correctional education and vocational programs have a 43% better chance of not returning to prison (Brower, 2015;Chappell, 2004;Irving, 2016;& Halkovic, 2014). These results demonstrate the value of such programs and should drive our justice system and correctional institutions to increase educational availability because of the possible impact on recidivism and the concurrent reduction of taxpayer burden to incarcerate citizens.…”
mentioning
confidence: 99%